Antioxidant and antimicrobial screening of isolated alkaloids from tinospora crispa - Hazrulrizawati, Abd Hamid; Roziasyahira, Mutazah; Izzah Hayati, Yahya; Zeyohannes, Senait Sileshi (Trans Tech Publications, 2021)
The antioxidant capacity by DPPH radical scavenging and antimicrobial activity by disk diffusion and broth microdilution method of nine isolated alkaloids from T. crispa were evaluated. All isolated alkaloids had been divided into three groups which were aporphine alkaloids, N-formylannonaine (1), N-formylnornuciferine (2), magnoflorine (9), oxoaporphine alkaloids, lysicamine (3) and liriodenine (4); and protoberberine alkaloids, columbamine(6), dihydrodiscretamine (7) and 4,13-dihydroxy-2,8,9-trimethoxydibenzo [a,g]quinolizinium (8). Protoberberine alkaloids showed (IC50 > 500-800 μg/mL) radical scavenging activity while oxaporphine alkaloids inhibited the growth of the Gram-positive bacteria, Staphylococcus aureus (+) and Enterococcus faecalis (+).The antioxidant and antimicrobial properties of different compounds support documented traditional use of T. crispa in wound healing and treatment of rheumatic, diarrhoea, ulcers, itches and wounds. Results of the present biological activity investigation further points to the potential of this plant species as a good source of natural antioxidant and preservative in food industry.